Seasonal sediment fluxes forcing supraglacial melting on the Wright Lower Glacier, McMurdo Dry Valleys, Antarctica. Issue 22 (4th July 2012) - MacDonell, Shelley A.; Fitzsimons, Sean J.; Mölg, Thomas
Abstract Cold‐based glaciers exist in low temperature and low humidity environments in which shortwave radiation is the largest source of energy to the glacier surface and the energy budget is very sensitive to the surface albedo. Consequently, the presence of relatively low volumes of debris on glacier surfaces has a significant impact on the timing, magnitude and rate of ablation at the surface. The aim of this study is to understand how the presence of sediment on the glacier surface at the start of the melt season can affect meltwater generation and delivery on a cold‐based glacier. A combination of field measurements, energy balance modelling and chemical mixing modelling were used on the Wright Lower Glacier, McMurdo Dry Valleys, Antarctica, between October 2005 and January 2006 to address this aim. In this system, sediment was transported onto the glacier surface during the winter months (March–October) by foehn winds, which reduced surface albedo at the start of the summer melt season. The areas of the glacier on which sediment accumulated began to melt earlier than other parts of the glacier and experienced a longer melt season. Over the study period, the total ablation on the dirty surfaces was nine times greater than for clean ice. Ablation on the dirty surfaces is dominated by melting, whereas sublimation dominates the clean ice. As the sediment was unevenly distributed over the glacier surface, the variation in melt amount and timing drove the development of a cryoconite hole system. Copyright © 2012 John Wiley & Sons, Ltd.